HUBUNGAN POLA MAKAN DENGAN STATUS GIZI PADA ANAK KELAS 4 DI SDN JABON 1 MOJOANYAR KABUPATENMOJOKERTO - Indatul Laili, Siti; Susanti, Aprilia (JURNAL KEPERAWATAN SEHAT, 2015)
Diet plays an important role in the nutritional status, especially for elementary school students. Menu of foods into balanced nutrition isneeded if the body wants in a healthy condition. The purpose of this study is to know to the connection between diet and nutritional status in student’s elementary school of forth grades at SDN 1 Jabon Mojoanyar Mojokerto. The research designis analytic correlation by using cross sectional approach. The population in this research are all students of forth grades at SDN 1 Mojoanyar Jabon include 41 students, in order the researcher decides to take all members of population to be sampling for this research totally 41 students.The independent variables of level diet and the dependent variable of nutritional status. The data is collection from questionnaires whereas it is taken from taking using Z-score criteria. The result of this research shows that 33 respondents (80,5%) have a sufficient diet, 32 respondents normal nutrition, and 1 respondent has more nutrition. The Spearment rho test values obtained rho ρ = 0.000 and α = 0.05 so that ρ <α then H0 is rejected. It means thereis connection between diet and nutritional status in student’s elementary school of forth grades at SDN 1 Jabon Mojoanyar Mojokerto. Good nutrition is necessary for the process in grow up of the children. Consumption many kinds of food, nutritional balanced and healthy areto complete individual nutritional for growing and developing body.Keywords: Diet, Nutritional Status